2020
DOI: 10.1016/j.xfre.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E administered to men in infertile couples on sperm and assisted reproduction outcomes: a double-blind randomized study

Abstract: Objective: To evaluate the influence on sperm parameters and in vitro fertilization (IVF) outcomes of the administration of 400 mg/day of vitamin E for 3 months to men from infertile couples who are undergoing IVF. Design: Double-blind, placebo-controlled, randomized study. Setting: Human reproduction unit of a university hospital. Patient(s): A total of 101 couples, 50 in the vitamin E group and 51 in the placebo group, undergoing IVF, among whom 64.4% of cases had an abnormal spermiogram according to World H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Vitamins D and E are lipid-soluble antioxidants and known to have protective effects on sperm quality and DNA integrity in rats challenged with oxidative stress ( Greco et al, 2005 ; Momeni and Eskandari, 2012 ). While vitamin E administration alone in men of infertile couples did not improve sperm parameters upon conventional sperm analysis ( Matorras et al, 2020 ), it did so when used in combination with selenium ( Keskes-Ammar et al, 2003 ). Regarding vitamin K, the endocrine function of the vitamin K-dependent Ca 2+ -binding protein osteocalcin in male reproduction has been reported ( Karsenty, 2011 ; Oury et al, 2011 ; Oury et al, 2013 ; Patti et al, 2013 ).…”
Section: Vitamins and Male Reproductionmentioning
confidence: 99%
“…Vitamins D and E are lipid-soluble antioxidants and known to have protective effects on sperm quality and DNA integrity in rats challenged with oxidative stress ( Greco et al, 2005 ; Momeni and Eskandari, 2012 ). While vitamin E administration alone in men of infertile couples did not improve sperm parameters upon conventional sperm analysis ( Matorras et al, 2020 ), it did so when used in combination with selenium ( Keskes-Ammar et al, 2003 ). Regarding vitamin K, the endocrine function of the vitamin K-dependent Ca 2+ -binding protein osteocalcin in male reproduction has been reported ( Karsenty, 2011 ; Oury et al, 2011 ; Oury et al, 2013 ; Patti et al, 2013 ).…”
Section: Vitamins and Male Reproductionmentioning
confidence: 99%
“…Lower serum α-tocopherol levels have been found in men with oligozoospermia and asthenozoospermia [ 36 ]. Matorras et al (2020) showed that vitamin E supplementation (400 mg α-tocopherol/day) for three months was positively associated with live birth rate and a trend towards better results in in vitro fertilization parameters, but it did not significantly increase progressive sperm cell motility in a double-blind, placebo-controlled, randomized study [ 39 ]. In another clinical trial with infertile men, Keskes-Ammar et al (2003) demonstrated that daily supplementation with vitamin E (400 mg) and selenium (225 μg) for three months improved sperm cell motility and decreased lipid peroxidation in sperm cell and seminal plasma [ 40 ].…”
Section: Diet and Male Reproductive Healthmentioning
confidence: 99%
“…The paper recently published in Human Reproduction Open by Joseph et al (2020) is one of a series of clinical trials which have been published in the past 12 months that purport to show little impact of antioxidant therapy on pregnancy rates ( Matorras et al ., 2020 ; Schisterman et al , 2020 ; Steiner et al , 2020 ). All of these trials have been well intentioned and carefully conducted however they all suffer from the same fundamental flaw which calls into question the validity of the conclusions reached ( Aitken, 2020a , b ).…”
mentioning
confidence: 99%